Pengaruh Dip Time Pada Unit Processor Terhadap Linearisasi Plate Cetak - Cholid Mawardi (Jurnal Poli-Teknologi, 2020)
This study aims to analyze the effect of the parameters on the processing unit on the quality of the printing plate. The parameters used in this study use the immersion time method. This research activity also aims to be able to know the real picture of the effect of changes in immersion time on the quality of the printed plate. Expected results of research on the effect of immersion time on the quality of printing plates, namely the extent to which immersion time affects the quality of Computer to Plate (CtP) plates to be printed on offset printing machines. Next, the researchers will also formulate problems that arise due to the development of plaques and provide solutions. This research should be a reference for users involved in improving print quality. For the printing industry can be used as a material consideration in the process of manufacturing quality printing plates for the good of the printing industry which is good at global competition.